The descriptive epidemiology of accelerometer-measured physical activity in older adults. Issue 1 (December 2016) - Berkemeyer, K.; Wijndaele, K.; White, T.; Cooper, A.; Luben, R.; Westgate, K.; Griffin, S.; Khaw, K.; Wareham, N.; Brage, S.
Abstract Background Objectively measured physical activity between older individuals and between populations has been poorly described. We aimed to describe and compare the variation in accelerometry data in older UK (EPIC-Norfolk) and American (NHANES) adults. Methods Physical activity was measured by uniaxial accelerometry in 4, 052 UK (49–91 years) and 3459 US older adults (49–85 years). We summarized physical activity as volume (average counts/minute), its underlying intensity distribution, and as time spent <100counts/minute, ≥809counts/minute and ≥2020counts/minute both for total activity and that undertaken in ≥10-min bouts. Results In EPIC-Norfolk 65 % of wear-time was spent at <100 counts/minute and 20 % spent in the range 100–500 counts/minute. Only 4.1 % of this cohort accumulated more than 30 min/day of activity above 2020 counts/minute in 10-min bouts. If a cut-point of >809 counts/minute is used 18.7 % of people reached the 30 min/day threshold. By comparison, 2.5 % and 9.5 % of American older adults accumulated activity at these levels, respectively. Conclusion As assessed by objectively measured physical activity, the majority of older adults in this UK study did not meet current activity guidelines. Older adults in the UK were more active overall, but also spent more time being sedentary than US adults.